2021
DOI: 10.1016/j.jot.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect and mechanism of QufengZhitong capsule for the treatment of osteoarthritis in a rat model

Abstract: Objective The purpose of this study was to evaluate the therapeutic effects and mechanism of Qufeng Zhitong (QFZT)capsule for the treatment of osteoarthritis (OA) in a rat model. Methods 8-10-week-old male Sprague–Dawley rats were randomly divided into the sham group (vehicle-treated), OA group (vehicle-treated), high-dose, middle-dose, low-dose of QFZT capsule -treated groups. OA was induced by transecting the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Osteoarthritis (OA) is the most common joint disease and the leading cause of disability. Cartilage lesions do not recover spontaneously, which eventually leads to cartilage degeneration and a vicious circle with OA. , Partial-thickness cartilage defects are hard to repair due to their irregular shapes and depth, lack of blood supply, and lack of a cell adhesion microenvironment . Recently, adhesive hydrogels have been widely studied for enhancing cartilage regeneration because the adhesion to host tissue could facilitate the integration of neo-tissue and host tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common joint disease and the leading cause of disability. Cartilage lesions do not recover spontaneously, which eventually leads to cartilage degeneration and a vicious circle with OA. , Partial-thickness cartilage defects are hard to repair due to their irregular shapes and depth, lack of blood supply, and lack of a cell adhesion microenvironment . Recently, adhesive hydrogels have been widely studied for enhancing cartilage regeneration because the adhesion to host tissue could facilitate the integration of neo-tissue and host tissue .…”
Section: Introductionmentioning
confidence: 99%
“…QZC could inhibit the expression of pulmonary fibrosis-related inflammatory factors such as IL-6, IFN- γ , TNF- α , and IL-17A to ease alveolitis and pulmonary fibrosis in the bleomycin-induced mouse pulmonary fibrosis model [ 19 ]. In addition, QZC can also be applied to treat various inflammatory diseases, such as osteoarthritis and frozen shoulder [ 20 , 21 ]. Therefore, in the present study, we employed network pharmacology to explore the correlation between the 16 identified compounds and their anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…QZC could inhibit the expression of pulmonary fibrosisrelated inflammatory factors such as IL-6, IFN-c, TNF-α, and IL-17A to ease alveolitis and pulmonary fibrosis in the bleomycin-induced mouse pulmonary fibrosis model [19]. In addition, QZC can also be applied to treat various inflammatory diseases, such as osteoarthritis and frozen shoulder [20,21].…”
Section: Characterization Of Chemical Constituents From Qzc and Explo...mentioning
confidence: 99%
“…OA is one of the most common joint diseases and is becoming a public health concern worldwide ( 1 ). At present, the treatment strategy for OA is mainly focused on relieving the symptoms ( 5 ). However, the underlying mechanisms of OA development remain to be fully elucidated, forcing the majority of patients with advanced OA to eventually require joint replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is frequently used to establish the OA model in vitro ( 4 ). At present, treatment methods for OA include surgery, physiotherapy and drug therapy ( 5 , 6 ). However, they can only relieve the symptoms of arthritis instead of effectively curing the condition in addition to being limited by the occurrence of adverse reactions ( 7 ).…”
Section: Introductionmentioning
confidence: 99%